2001
DOI: 10.2169/internalmedicine.40.736
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Associated with Superior Mesenteric Artery Syndrome: Report of Two Cases.

Abstract: Weobserved two patients with diabetes whowere suffering from nausea, vomiting and epigastralgia after meals. These symptoms subsided when lying on their left side. Since the 2 patients had autonomic neuropathy, at first, the symptoms seemed to be attributable to diabetic gastroparesis. However, they were diagnosed as having superior mesen-teric artery syndrome by hypotonic duodenography. These finding suggest that in diabetic patients whohave a history of excessive weight loss superior mesenteric artery syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…Because the symptoms of diabetic gastroenteropathy mimic those of SMAS, the detection of SMAS might be delayed (14)(15)(16). In the present case, an autonomic nervous disorder due to diabetic neuropathy might have occurred due to the decreased peristalsis of the digestive tract, which might worsen the digestive symptoms of SMAS.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Because the symptoms of diabetic gastroenteropathy mimic those of SMAS, the detection of SMAS might be delayed (14)(15)(16). In the present case, an autonomic nervous disorder due to diabetic neuropathy might have occurred due to the decreased peristalsis of the digestive tract, which might worsen the digestive symptoms of SMAS.…”
Section: Discussionmentioning
confidence: 70%
“…In an upper gastrointestinal contrast study the incidence of SMAS was reported to be approximately 0.2%; however, the actual prevalence of SMAS remains unclear (12)(13)(14). To the best of our knowledge, there are only three reports on diabetes complicated by SMAS (14-16).…”
Section: Discussionmentioning
confidence: 99%
“…To date, six cases of SMAS associated with diabetes (three reports of type 1 diabetes and two reports of type 2 diabetes) have been reported (Table 2) (9,(25)(26)(27)(28). Of note, a recently reported case of SMAS in a diabetic patient from weight loss due to SGLT2 inhibitors implied that body weight loss is a pivotal aspect for this pathology (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present patient, the bowel sounds were decreased on admission because of gastroparesis as a result of diabetic autonomic neuropathy. There are several reports of SMA syndrome in patients with diabetes [6][7][8] . In some patients with diabetic autonomic neuropathy, it has been reported that it is difficult to distinguish gastroparesis from SMA syndrome on initial diagnosis 6,7 .…”
Section: Discussionmentioning
confidence: 99%